THE CALCULATION OF THE TARIFF FOR EXPRESS DELIVERY WITH ADDITIONAL COSTS - Levytskyi, I. Ye. (Science and Transport Progress, 2003)
Railway transport, as a producer of a wide range of logistic services, offers the transport services market delivery of freights at a shortened time or transportation services with differentiated periods of delivery.